Irans Water Crisis; Inducers, Challenges and Counter-Measures - Kaveh Madani Larijani (European Regional Science Association (ERSA), 2005)
Similar to many countries in the world experiencing extreme water shortages, the Islamic Republic of Iran is also in the midst of a serious water crisis. The looming crisis is being blamed on a number of factors including population growth and uneven distribution, natural phenomena such as droughts and changing climate patterns, and the mismanagement of existing water resources. The country's resources management is facing many subsequent challenges, including growing demand for water resources with proper quality, a considerable increase in the costs of supplying additional water and urgent need to control water pollution as well as the uncontrolled exploitation of underground waters and the necessity to conserve these valuable resources. If immediate mitigation measures are not taken, the situation could become even more disastrous in the years to come. Being cognisant of the crisis' importance and its destructive influences, governmental authorities have begun evaluating their plans and programmes and have devised long-term strategies to allay the water crisis. This article describes the state of the country's threatening water crisis while also explaining in detail its main sources and the subsequent challenges it has caused the country to endure. Discussions on how governmental authorities are fighting the crisis and the state of the approaches which they have pioneered are also presented. Moreover, context of the Long-term Development Strategies for Iran's Water Resources is discussed from sustainable water mangement point of view with practical recommendations on the issue.
Keywords: 330